Environmental Activism Through Instagram (A Study of the Global Climate Strike Campaign by Greenpeace Indonesia) - Zainubi, Hilman Haikhal; Ciptadi, Suluh Gembyeng (International Journal of Environmental Communication (ENVICOMM), 2024)
Instagram is one of the social media products used by non-governmental organizations, Greenpeace Indonesia, in conducting the Global Climate Strike campaign. This study investigates the digital activism strategies employed by Greenpeace Indonesia in executing the Global Climate Strike campaign on Instagram. Adopting a descriptive qualitative research approach within a constructivist paradigm, the study gathered data through interviews and documentation. The research is guided by the concept of digital media and environmental activism, focusing on the dimensions of alert, amplify, and engage. Three interviewees contributed insights into Greenpeace Indonesia's communication practices, while documentations were used to support and validate the findings. The study's results indicate that Greenpeace Indonesia applied the three stages—alert, amplify, and engage—in their campaign. The alert stage served as an initial step to disseminate information, the amplify stage involved strategies to effectively communicate campaign messages to the public, and the engage stage facilitated the accommodation of public aspirations through social media interaction.